Strength and push gait asymmetry in skeleton athletes - Gong, M.; Liu, Y.; Cao, Z.; Gao, B. (Journal of Human Kinetics, 2025)
The aim of this study was to explore how lower limb strength and push gait asymmetry affected performance of skeleton athletes. Isokinetic strength of the bilateral lower limb was measured in sixteen skeleton athletes. Kinematic and kinetic data were also collected during pushing. The asymmetry of lower limb strength and the push gait were measured using the symmetry angle. Asymmetry existed in the strength of the lower limbs and the push gait of skeleton athletes. The symmetry angle of peak torque of ankle dorsiflexion at 60°/s (r = -0.48, p = 0.06) and contact time (r = -0.48, p = 0.06) was moderately negatively correlated with mean push velocity, but the center of gravity height (r = 0.50, p = 0.05) and the hip joint angle (r = 0.54, p = 0.03) at the touchdown showed a moderate positive correlation with mean push velocity. The asymmetry of lower limb strength and the push gait in skeleton athletes is specialized. Reducing the difference in peak torque of dorsiflexion between both sides, as well as the disparity in contact time during the push phase, may be beneficial in enhancing push velocity.